The handbook to IFRS transition and to IFRS U.S. GAAP dual reporting : interpretation, implementation and application to grey areas - Bellandi, Francesco (Chichester : John Wiley, 2012)
Some portions are excerpted from Accounting for equity and other comprehensive income, dual reporting under U.S. GAAP and IFRS (e-book) by Francesco Bellandi. Cf. copyright page.
Includes bibliographical references and index.
Keywords: Financial statements -- Standards -- United States; Accounting -- Standards -- United States; BUSINESS & ECONOMICS -- Accounting -- Standards (GAAP, IFRS, etc.); Accounting -- Standards; Financial statements -- Standards; United States; Electronic books